The Memory and Affective Flexibility Task: a new behavioral tool to assess neurocognitive processes implicated in emotion-related impulsivity and internalizing symptoms - Allen, Kenneth J. D.; Elliott, Matthew V.; Ronold, Eivind H.; Rajgopal, Nandini A.; Hammar, Åsa; Johnson, Sheri L. (Frontiers in Psychiatry, 2025)
BackgroundCognitive rigidity and working memory impairment are established features of internalizing syndromes. Growing evidence suggests that deficits in affective control –cognitive control in the context of emotion – may underpin elevated emotion-related impulsivity in various psychiatric disorders.ObjectiveThis study examines two components of affective control (affective flexibility and emotional working memory) as potential neurocognitive processes linking emotion-related impulsivity to internalizing psychopathology.MethodUndergraduate participants (analysis n = 120) completed the Memory and Affective Flexibility Task (MAFT), a novel behavioral assessment designed to assess hot cognition in affective flexibility and emotional working memory performance, alongside self-report measures of impulsivity and symptoms of internalizing disorders.ResultsStructural equation modeling suggested that less accurate working memory during neutral trials (cool cognition) was associated with more symptoms of internalizing psychopathology. However, effects of hot working memory and affective flexibility were not significantly related to emotion-related impulsivity or psychopathology scores.ConclusionsAlthough findings provide no support for the validity of MAFT indices of hot cognition, these results replicate and extend work on the importance of cool working memory and emotion-related impulsivity as correlates of psychopathology.